2021
DOI: 10.1177/09544070211064474
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the compressor for gas-entraining diffuser EGR

Abstract: Exhaust Gas Recirculation (EGR) is an effective way to reduce nitrogen oxide (NO x) emissions, and the EGR application increases the engine backpressure to some extent. In this paper, a new EGR method named gas-entraining diffuser EGR was proposed to reduce pumping loss. It introduces the exhaust gas into the compressor diffuser inlet where the static pressure is the lowest without blades fouled by exhaust gas. As a result, lower pressure at the turbine upstream can achieve EGR. Then, a newly designed induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…11 In addition, to meet the stringent requirements of the main emission limits of China VI, 12,13 a higher EGR rate is required for reducing the cost of tail gas after-treatment systems by suppressing NO x generation. To further reduce the pumping loss and increase the EGR rate, a gas-entraining diffuser EGR is proposed in Zhu et al, 14 which introduces exhaust gas into the diffuser inlet where the static pressure is the lowest to achieve HP-EGR without fouling of the compressor blades by exhaust gas. Meanwhile, a new induced structure has been designed to meet the needs of the new EGR so that a large amount of exhaust gas enters the diffuser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, to meet the stringent requirements of the main emission limits of China VI, 12,13 a higher EGR rate is required for reducing the cost of tail gas after-treatment systems by suppressing NO x generation. To further reduce the pumping loss and increase the EGR rate, a gas-entraining diffuser EGR is proposed in Zhu et al, 14 which introduces exhaust gas into the diffuser inlet where the static pressure is the lowest to achieve HP-EGR without fouling of the compressor blades by exhaust gas. Meanwhile, a new induced structure has been designed to meet the needs of the new EGR so that a large amount of exhaust gas enters the diffuser.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of comprehensive studies on compressor performance and energy loss by injection. Regarding the effect of the induced structure on the compressor, Zhu et al 14 only studied the effect of the induced angle on the compressor, and the results showed that the induced gas caused a reduction of up to 7% in the compressor efficiency, the primary loss occurred at the diffuser, and the induced structure had an obvious effect on the static pressure of the induced structure inlet. Therefore, further studies are needed to obtain the best induced structure design.…”
Section: Introductionmentioning
confidence: 99%